Blended Learning: enabling Higher Education Reform - Matheos, Kathleen; Cleveland-Innes, Martha (Revista Eletrônica de Educação, 2018)
Abstract Blended learning research and practice have been areas of growth for two decades in Canada, with over 95% of Canadian higher education institutions involved in some form of blended learning. Despite strong evidence based research and practice blended learning, for the most part, has remained at sidelined in Canadian universities. The article argues the need for blended learning to situate itself within the timely and crucial Higher Education Reform (HER) agenda. By aligning the affordances of blended learning with the components of HER, blended learning can clearly serve as an enabler for HER. Keywords: Blended learning, Higher Education Reform. References AKYOL, Z.; GARRISON, D. R.; OZDEN, M. Y. Online and blended communities of inquiry: Exploring the developmental and perceptional differences. The International Review of Research in Open and Distributed Learning, 10(6), 65-83, 2009. ALLEN, I. E.; SEAMAN, J. Going the distance: Online education in the United States, 2011. Babson Survey Research Group, 2010. Retrieved from: http://sloanconsortium.org/publications/survey/going_distance_2011. ALLEN, I. E.; SEAMAN, J. Online report card—tracking online education in the United States. Babson Survey Research Group, Online Learning Consortium, 2016. Retrieved November 27, 2016, from http://onlinelearningconsortium.org/read/online-report-card-tracking-online-education-united-states-2015/ CLEVELAND-INNES, M.; GAUVREAU, S. Faculty role change: Adjustment to the influence of online teaching and learning. European Journal of Open, Distance, and eLearning, EDEN Special Issue, 134-144, 2015. Retrieved from: http://www.eurodl.org/materials/special/2015/Cleveland-Innes_Gauvreau.htm COHERE Report on Blended Learning HRSDC Canada, 2011. Available at http://cohere.ca/ GARRISON, D.R.; VAUGHAN, N.D. Institutional change and leadership associated with blended learning innovation: Two case studies. The Internet and Higher Education, 2013. GARRISON, D.R. University of Calgary Position Paper. Blended Learning Approaches to Teaching and Learning, 2003. GARRISON, D. R.; VAUGHAN, N. Blended learning in higher education. San Francisco: Jossey-Bass, 2008. GARRISON, D. R. E-Learning in the 21st century: A framework for research and practice (2nd Ed.). London: Routledge/Taylor and Francis, 2011. GARRISON, D. R.; KANUKA, HBlended learning: Uncovering its transformative potential in higher education. The internet and higher education, 7(2), 95-105, 2004. Retrieved from: http://dx.doi.org/10.1016/j.iheduc.2004.02.001 GRAHAM, C. R.; WOODFIELD, W.; HARRISON, J. B. A framework for institutional adoption and implementation of blended learning in higher education. The Internet and Higher Education, 18, 4–14, 2013. Retrieved from: doi:10.1016/j.iheduc.2012.09.003 INTERNATIONAL Review of Research in Open and Distributed Learning Volume 18, Number 3 May – 2017. Marti-Cleveland-Innes Leadership Notes: Editorial HARTMAN, J. The Promise and Practice of Blended Learning. 2010. Retrieved from: http://hosted.mediasite.com/mediasite/Viewer/?peid=b093b6024bb349feae7ba771bd29d9b61d LAUMAKIS, M.; GRAHAM, C.; DZIUBAN, C. The Sloan-C Pillars and boundary objects in framework for evaluating blended learning. Journal of Asynchronous Learning Networks, 13(1), 75-87, 2010. LÓPEZ-PÉREZ, M.V.; PÉREZ-LÓPEZ, M.C.; RODRÍGUEZ-ARIZA, L. Blended learning in higher education: Students’ perceptions and their relation to outcomes. Computers & Education, 56(3), 818-826. (2011). MOSKAL, P.; DZIUBAN, C.; HARTMAN, J. Blended learning: A dangerous idea?. TheInternet and Higher Education, 18, 15-23, 2013. http://dx.doi.org/10.1016/j.iheduc.2012.12.001. OWSTON, R. Blended learning policy and implementation: Introduction to the special issue. The Internet and Higher Education, 18, 1-3, 2013. http://dx.doi.org/10.1016/j.iheduc.2013.03.002. PICCIANO, A. G. Blended with purpose: The multimodal model. Journal of Asynchronous Learning Networks, 13(1), 7-18. (2009). VAUGHAN, N.D.; GARRISON, D.R. A blended faculty community of inquiry: Linking leadership, course redesign and evaluation. Canadian Journal of University Continuing Education, 32 (2), 67-92, 2006. Retrieved from : http://www.extension.usask.ca/cjuce/articles/v32pdf/3223.pdf VAUGHAN, N. A blended community of inquiry approach: Linking student engagement and course redesign. The Internet and Higher Education, 13 (1-2), 60-65, 2010. VAUGHAN, N. D.; CLEVELAND-INNES, M.; GARRISON, D. R. Teaching in blended learning environments: Creating and sustaining communities of inquiry. Athabasca University Press, 2013. VAUGHAN, N.; CLOUTIER, D. Evaluating a blended degree program through the use of the NSSE framework. British Journal of Educational Technology, 48: 1176–1187, 2017. doi:10.1111/bjet.12537 WALLACE, L.; YOUNG, J. Implementing blended learning: Policy implications for universities. Online Journal of Distance Learning Administration, 13(4), 2010. Retrieved from http://www.westga.edu/ distance/ojdla/winter134/wallace_young134.html WILLCOX et al. On Line Education: A Catalyst for H.E. Reforms. Willcox, K., Sarma, S., & Lippel, P. Online education: A catalyst for higher education reform. Cambridge: MIT, 2016. Retrieved from: https://oepi.mit.edu/sites/default/files/MIT%20Online%20Education%20Policy%20Initiative%20April%202016_0.pdf ZHANG, W.; ZHU, C. Review of blended learning: Identifying key themes and categories. International Journal of Information and Education Technology, 2017. doi: 10.18178/ijiet.2017.7.9.952